Synthesis of graphene oxide dots coated biomatrices and its application for the removal of multiple pollutants present in wastewater. (1st December 2018) - Manna, Suvendu; Bhattacharya, Sandipan; Sengupta, Shubhalakshmi; Das, Papita
Abstract: Synthesis of a suitable adsorbent with multiple pollutants removal capacity could be a perfect solution to all water related pollution. This article presents a promising case, where graphene oxide dots (GOD) had been used to coat two different biomatrices and used to remove pollutants like dyes, fluoride, biomolecules and bacteria. The results indicated that after GOD coating the dyes and fluoride removal efficiency for both the biomatrices enhanced around 2–3 times than their untreated counterparts. Also protein removal efficiency of jute enhanced from 10% to around 70% after GOD coating. Similarly, bacteria removal efficiency of both the jute and chitin biomatrices enhanced more than 75%. Also, it was noticed that the preparation of GOD coated biomatrices were cost-effective and technically sound than the GO and GOD based alternatives. However, further study in detail is essential to establish the usability of the materials in multiple pollutants removal from water in large scale. Highlights: Graphene oxide dots (GOD) were synthesized using simple process. Bomatrices coated with GOD were used for wastewater treatment. GOD coated biomatrices showed multiple types of pollutants removal efficacy including bacteria. The GOD coated biomatrices were economic and technically superior relatively.